ANALISIS LAPORAN KEUANGAN KONSOLIDASIAN INTERIM PT. BUMI RESOURCES MINERALS Tbk DALAM MENGUKUR KINERJA KEUANGAN - Izza Karunia Putri; Julianto (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2023)
The aim of this research is to understand the potential of PT. Bumi Resources Minerals Tbk in managing the company's business and performance in utilizing assets to generate profits. Knowing changes in financial position in a period, projecting what the business will be like in the next period and assessing the ongoing business performance. This research uses literature studies from trusted sources to present credible data. On July 1 2019, this company has changed its main business activities from the investment company industry to coal mining. This company has subsidiary affiliates including Calipso Investment Pte Ltd. And subsidiaries, International Minerals Company, LCC, Lemington Investments Pte Ltd., PT. Bumi Sumberdaya Semester (formerly PT. Multi Regional Compete), PT. Citra Palu Minerals, PT. Multi Capital and subsidiary, PT. Sarkea Prima Minerals. Company Development PT. Bumi Resources Mineral Tbk by comparing the times on March 31 2023 and December 31 2022 experienced changes in operational improvements and profits obtained from existing financial reports, so that with other subsidiaries this parent company is growing rapidly. Keywords: PT. Bumi Resources Mineral Tbk, Analysis of Financial Statements, Companies, Mines, Coal Mines